1986
DOI: 10.1007/bf00033928
|View full text |Cite
|
Sign up to set email alerts
|

Application of a hybrid finite element method to determine stress intensity factors in unidirectional composites

Abstract: In this paper a hybrid finite element method is applied in evaluation of the stress intensity factors K I and KII of unidirectional fiber reinforced composites. In order to satisfy the stress singularity at the crack tip a singular super-element based on a modified complementary energy principle is developed. The stress and displacement fields in the super-element are expressed in terms of polynomials of two complex variables ~1 and ~ in the transformed ~-plane. The stiffness matrix of the super-element was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 4 publications
(7 reference statements)
0
17
0
Order By: Relevance
“…The stress and displacement fields around the crack-tip can be composed by these parameters. This method was first used to develop a singular element for cracked composite problems (Khalil et al, 1986), its reliability has been substantiated by comparing against results from the J-integral approach (Ju, 1996), and subsequently applied to determine stress intensity factors in orthotropic composites (Ju, 1996;Ju and Rowlands, 2003a,b).…”
Section: Thermoelastic Stress Analysis Of Cracked Compositesmentioning
confidence: 99%
“…The stress and displacement fields around the crack-tip can be composed by these parameters. This method was first used to develop a singular element for cracked composite problems (Khalil et al, 1986), its reliability has been substantiated by comparing against results from the J-integral approach (Ju, 1996), and subsequently applied to determine stress intensity factors in orthotropic composites (Ju, 1996;Ju and Rowlands, 2003a,b).…”
Section: Thermoelastic Stress Analysis Of Cracked Compositesmentioning
confidence: 99%
“…Khalil et al [ 1 ] showed that the displacements near the crack tip in an anisotropic material can be…”
Section: Displacements Near the Crack Tipmentioning
confidence: 99%
“…Khalil et al [1] generated a hybrid finite element to evaluate the stress intensity factors of anisotropic materials. Chen and Atluri [2], and Lee and Wang [3] presented the finite element method to determine weight functions for orthotropic cracked bodies, and then the stress intensity factors were calculated using the weight functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, independent of these difficulties and due to their sound theoretical bases, the equilibrium hybrid elements as used in fracture mechanics have been used with success in several areas. Among these areas, one can cite composite and anisotropic material applications [44,45], thermo-elastic applications [46], and determination of the T-stress factor [47] and three-dimensional analysis [48].…”
Section: Introductionmentioning
confidence: 99%